(untitled) (European Journal of Economics, Finance and Business Development, 2025)
This article examines the transformative impact of digital technologies on entrepreneurship, highlighting how innovations in technology have changed business models, market access, and operational efficiency for entrepreneurs. By analyzing a variety of digital tools and platforms, the study reveals ways in which these technologies can lower barriers to entry for new businesses, facilitate customer acquisition, and improve data-driven decision-making. The article also examines the challenges entrepreneurs face in adapting to rapid technological change, including cybersecurity challenges and the need for continuous learning.